RARE EARTH ELEMENTS AND THEIR USE IN THE NATIONAL ECONOMY - Makhmudova Star Farkhodzhan's daughter (Scientific Impulse, 2023)
В данной статье рассмотрено редкоземельные элементы и их использование в народном хозяйстве.